2016
DOI: 10.1016/j.jchf.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Intrarenal Hemodynamic Evaluation by Doppler Ultrasonography in Heart Failure

Abstract: IRVF patterns, rather than RI, depended on RAP, suggesting a correlation with renal congestion. In addition, IRVF patterns strongly correlated with clinical outcomes independent of RAP and other risk factors and might provide additional information to stratify vulnerable HF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
225
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(267 citation statements)
references
References 30 publications
8
225
0
7
Order By: Relevance
“…Marked increases in IVCD, LAD and biphasic intrarenal vein flow pattern were seen at the time of marked bradycardia, suggesting the occurrence of increased CVP and preload. The biphasic intrarenal vein flow pattern is likely to occur in patients with increased CVP 8. These indicated that increase in the central fluid volume occurred in this patient.…”
Section: Discussionmentioning
confidence: 65%
“…Marked increases in IVCD, LAD and biphasic intrarenal vein flow pattern were seen at the time of marked bradycardia, suggesting the occurrence of increased CVP and preload. The biphasic intrarenal vein flow pattern is likely to occur in patients with increased CVP 8. These indicated that increase in the central fluid volume occurred in this patient.…”
Section: Discussionmentioning
confidence: 65%
“…13, 14 Patients in each group were further divided into 2 subgroups according to the presence or absence of anemia.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…This pattern may identify patients in the early phase of renal congestion. Differently from the study of Iida et al[45], there were no prognostic differences between polyphasic and monophasic intermittent patterns, they are both related to worse venous congestion and identify patients at higher risk[46]. …”
Section: Renal Venous Echo Doppler and Venous Patternsmentioning
confidence: 83%
“…Iida et al[45] evaluate intrarenal venous flow and VII in a population of outpatients and hospitalized patients affected by heart failure. They found three vein flow patterns: Continuous, biphasic discontinuous and monophasic discontinuous.…”
Section: Renal Venous Echo Doppler and Venous Patternsmentioning
confidence: 99%
See 1 more Smart Citation